PERBANDINGAN KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH DI KECAMATAN DENPASAR SELATAN KOTA DENPASAR PADA 10 TAHUN MENDATANG - Ida Bagus Suryatmaja; Krisna Kurniari; I Made Nada; Frederikus Marung (Jurnal Ilmiah Kurva Teknik, 2021)
Increased population, directly proportional to the increase in clean water needs. It also affects the availability of clean water both for current needs and for future time. To ensure that the availability of clean water can meet the needs of 2030, a study is needed to find out how much availability of clean water in 2030 and what needs are needed. To find out, a proper calculation method is needed. In this study, the availability of clean water in 2030 was calculated using the geometry method. Before calculating it, data on clean water availability was needed in the previous few years to find out the average growth of water availability which subsequently using geometry methods can be known to the availability of water by 2030. The results of the calculation showed that the availability of clean water in 2030 was 336.62 liters/second. Meanwhile, to calculate the need for clean water calculated using data on average clean water requirements today was then analyzed by the estimated population in 2030. The result was, the need for clean water in 2030 with the level of population at that time was 668,7756 liters/second. It can be concluded, the need for clean water in 2030 is greater than the availability of clean water. Therefore, looking for other important clean water sources is planned as early as possible so that water needs by 2030 are still fulfilled.